Ethylene mediates CuO NP-induced ultrastructural changes and oxidative stress in Arabidopsis thaliana leaves. Issue 3 (3rd February 2020) - Azhar, Wardah; Khan, Ali Raza; Muhammad, Noor; Liu, Bohan; Song, Ge; Hussain, Akhlaq; Yasin, Muhammad Umair; Khan, Sulaiman; Munir, Raheel; Gan, Yinbo
Abstract : Metallic oxide nanoparticles (NPs) have received great importance due to their unique properties and valuable applications in various fields. Abstract : Metallic oxide nanoparticles (NPs) have received great importance due to their unique properties and valuable applications in various fields. The release of nanoparticles into the environment at a large scale has become a serious threat to the ecosystem especially plants. Various reports have illustrated the toxicity of CuO NPs to plants, but the hypothesis underlying ethylene-mediated CuO NP toxicity is still unknown. The present study was conducted to investigate the response of ethylene-insensitive mutants ( ein2-1, ein4 and etr1-3 ) and WT under CuO NP exposure. The results of the present study showed that CuO NPs adversely affected the biomass, chlorophyll contents, guard cells, stomatal aperture and other cell organelles, with consequent decline in plant biomass. Moreover, CuO NPs significantly increased ROS accumulation and induced toxicity in the leaves of all four genotypes. However, ethylene-insensitive mutants markedly showed less sensitivity to this damage as compared to WT seedlings. More importantly, higher levels of CuO NPs significantly increased the activity of ethylene reporter EBS::GUS lines and the transcript level of ethylene signaling and biosynthesis genes. Furthermore, the expression levels of antioxidant enzyme related-genes were slightly enhanced by the exogenous application of ethylene biosynthesis and perception antagonists cobalt (Co 2+ ) and silver (Ag + ), respectively, than the treatment with CuO NP stress alone. In contrast, it is significantly suppressed by an ethylene biosynthesis precursor (ACC), which further provided evidence that ethylene participates in CuO NP-induced oxidative damage and growth reduction in Arabidopsis thaliana leaves.